Three-partite need analysis to design crosscultural coursebook for Islamic higher education: Mixed-method - Istiqamah, Istiqamah; AR, Nurmy; Keuk, Chan Narith (UPT Bahasa Universitas Tanjungpura, 2024)
This research aimed to investigate the needs of the curriculum, teachers, and learners for a cross-cultural course book implementing mixed methods. It enlisted 6 teachers and 42 learners as respondents. Documents and questionnaires were data collection techniques that were analyzed quantitatively and qualitatively. The findings indicated that the curriculum implemented the global-local approach and competency-based curriculum. Teachers experienced a rich English culture and expected that the course book design would include values such as more attention to openness, flexibility, humility, and a sense of humour and less on a spirit of adventure. They selected electronic over non-electronic materials and five topics. In addition, learners experienced literal text comprehension. They also expected that it included concepts on culture, electronic over non-electronic materials, and learning resources consecutively arranged, such as articles, videos, posters, PPTs, books, and others (newspapers, magazines). To conclude, the investigation on the needs of the cross-cultural course book design implemented a three-partite need analysis model involving curriculum, teachers, and learners, which is also the novelty of this research. They contributed to shaping the design: a global and local approach, competency-based curriculum, topical and value-oriented, electronic-oriented materials, and multiple learning resources.